A Matéria do Projetar - Calamity Atelier (Arte Sella). Young Architects Competitions - Sofia Moreira Martins (2019)
Nature can be both a mother and a cruel stepmother. On October 29, 2018, a violent storm hit like the mountains, where Art Sella cultural association is located, in Borgo Valsugana, Italy, devastating acres of secular forest and destroying half of the artwork in the art park. In a post-natural disaster context, a need for planning and a new program were urgent, which led the cultural association to join the Young Architects Competitions international contest, launching the Calamity Atelier in search of ideas for regeneration of the largest art park in the contemporary world. The participation in the contest coupled with the realization of this work, which aims to answer the problems that motivated Calamity Atelier and aims to develop the architecture project and practical and conceptual problems related to the project, in an attempt to recognize tools and mechanisms of response, conscious or subconscious, adopted throughout the creative process. Thus, the purpose of the work coincides with the goal of the architectural project itself - answer to a specific problem, program, and needs - but also the way of thinking and doing architecture, seated in physical and sensorial comprehension of place with high landscape value, where the architectural work must emerge as a mediator of the relationship between Man, Art and Nature. The research is done by exposing a personal design practice, not as a systematic process, but rather as an intellectual and intuitive process, highlighting the most relevant design options and themes, integrated into a structure that reflects both project phases in time as the formulation of the present dissertation, corresponding to three moments: the initial contextualization of the problem and program, the project during the contest and the project after the contest. Thus, the skeleton of the structure is associated with the chronological order of the work process and results from the strong practicality expressed in it. The theoretical-practical reflection is built from (and simultaneously) the architectural project and its creative process, which constituted in itself the beginning, the middle and the end of the dissertation and culminates in the final proposal, not as a drawn conclusion from a previous theoretical study, but rather as a starting point for thinking about designing places.